Negative pole piece, battery and electric equipment

By alternately setting active material coatings of different particle sizes on the surface of the current collector, the ion transmission path of the lithium-ion secondary battery is optimized, the problem of laser hole damage to the material structure is solved, and the dynamic performance and energy density of the battery are improved.

CN119480906AActive Publication Date: 2025-02-18ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411457996.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In lithium-ion secondary batteries, high-pressure density negative electrode sheet material is easily damaged during laser drilling, resulting in the shedding of active substances and increased electrochemical reactions, which damages the safety and cycle life of the battery.

Method used

By alternately setting the active material particles in the second direction on the surface of the current collector, the first active coating and the second active coating have different particle sizes, so that the characteristics of the first active coating and the second active coating are different, and Ds2/Ds1≤ 0.5, D502/D501≥1.3, to optimize the ion transmission path inside the battery.

Benefits of technology

It effectively improves the dynamic performance of the battery cell, reduces the risk of analytical phenomena, and does not damage the material structure, improving the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480906A_ABST
    Figure CN119480906A_ABST
Patent Text Reader

Abstract

The invention discloses a negative pole piece, a battery and electric equipment, the negative pole piece comprises a current collector, the thickness direction of the current collector is a first direction; the negative active material layer is arranged on at least one surface of the current collector; the negative electrode active material layer comprises a first active coating and a second active coating which are alternately arranged in a second direction perpendicular to the first direction, and the first active coating and the second active coating meet the following conditions: Ds2 / Ds1 < = 0.5 and D502 / D501 > = 1.3, so that the material structure is not damaged while the risk of a disruption phenomenon can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode plate, a battery and an electrical device. Background Art

[0002] In lithium-ion secondary batteries, improving battery energy density is one of its important goals. When the battery energy density is improved, it is usually accompanied by an increase in the thickness of the active material coating on the negative electrode and an increase in the compaction density. However, with the increase in coating thickness and the increase in compaction density, the kinetic characteristics of the battery cell will be significantly affected, resulting in obstructed ion transmission during charging, increasing the risk of ionization phenomena, and may further damage the safety and cycle life of the battery. In related technologies, in order to alleviate this problem, laser drilling technology has been introduced as an innovative means to improve the kinetic performance of battery electrodes by physical means. This method uses a laser beam to perform precise ablation on a high compaction density electrode material to form a microporous structure. These micropores serve as permeation channels for the electrolyte, effectively promoting the diffusion efficiency of lithium ions, thereby optimizing the ion transmission path inside the battery.

[0003] Nevertheless, laser drilling technology also faces challenges in practical applications, especially its potential destructiveness to active materials cannot be ignored. For example, the current mainstream silicon-carbon negative electrode materials are usually prepared by vapor deposition, that is, embedding elemental silicon into a porous carbon matrix to improve the energy storage capacity and cycle stability of the negative electrode. However, the high temperature and high-energy laser beam generated during the laser drilling process often destroy the carbon matrix structure of the silicon-carbon composite material, causing the elemental silicon originally wrapped by the carbon matrix to be directly exposed to the electrolyte. This direct exposure not only aggravates the shedding of active materials, but may also trigger a series of adverse electrochemical reactions, such as increasing the self-discharge rate of the battery, shortening the cycle life of the battery, and negatively affecting the overall performance of the battery. Therefore, how to reduce the risk of electrochemical phenomena without destroying the material structure has become an urgent problem to be solved. Summary of the invention

[0004] The embodiments of the present application provide a negative electrode plate, a battery, and an electrical device that can reduce the risk of thermal decomposition without destroying the material structure.

[0005] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising:

[0006] A current collector, wherein the thickness direction of the current collector is a first direction;

[0007] A negative electrode active material layer is disposed on at least one surface of the current collector;

[0008] The negative electrode active material layer includes a first active coating layer and a second active coating layer alternately arranged in a second direction perpendicular to the first direction, and the first active coating layer and the second active coating layer satisfy: Ds2 / Ds1≤0.5, D502 / D501≥1.3, wherein Ds2=D902-D102, Ds1=D901-D101;

[0009] D101 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 10%, D501 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 50%, D901 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 90%, D102 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 10%, D502 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 50%, and D902 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 90%.

[0010] According to the negative electrode plate of the embodiment of the first aspect of the present application, there are at least the following beneficial effects: by alternately arranging the first active coating and the second active coating with different particle sizes of active material particles on the surface of the current collector along the second direction, the characteristics of the first active coating and the second active coating are different. Wherein, by controlling Ds2 / Ds1≤0.5, D502 / D501≥1.3, the particle size of the second active coating is relatively large, which is conducive to the storage of the electrolyte, and the ion impedance is low, which can provide an ion channel for the movement of ions, and can effectively improve the kinetic performance of the battery cell, reduce the electrolyte transport path of the first active coating, and improve the kinetic performance. At the same time, because the particle size of the first active coating is relatively small and the compaction density is large, the energy density of the battery can be improved. Therefore, the negative electrode plate provided in the embodiment of the present application can effectively reduce the risk of analyte phenomenon without destroying the material structure.

[0011] According to some embodiments of the first aspect of the present application, in the alternating direction of the first active coating and the second active coating, the width of the first active coating is W1 mm, the width of the second active coating is W2 mm, and W1 / W2≤5.

[0012] According to some embodiments of the first aspect of the present application, 0.1≤Ds2 / Ds1≤0.5; and / or, 1.3≤D502 / D501≤2; and / or, 1.5≤Ds2≤10.

[0013] According to some embodiments of the first aspect of the present application, in the alternating direction of the first active coating and the second active coating, the width of the first active coating is W1 mm, the width of the second active coating is W2 mm, 1≤W1 / W2≤5; and / or the width W2 mm of the second active coating is 1-3 mm.

[0014] According to some embodiments of the first aspect of the present application, the active material of the first active coating layer and the active material of the second active coating layer are independently selected from at least one of artificial graphite, natural graphite, hard carbon and silicon-based materials.

[0015] According to some embodiments of the first aspect of the present application, the active substance of the first active coating and the active substance of the second active coating are the same substance; and / or, the active substance of the first active coating and the active substance of the second active coating include silicon-based materials.

[0016] According to some embodiments of the first aspect of the present application, the silicon-based material includes a silicon-carbon material.

[0017] According to some embodiments of the first aspect of the present application, the first active coating and the second active coating further include a conductive agent and a binder; the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene, and the binder includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, and polymethyl methacrylate.

[0018] In a second aspect, an embodiment of the present application provides a battery, comprising the negative electrode plate as described in the embodiment of the first aspect.

[0019] In a third aspect, an embodiment of the present application provides an electrical device, comprising a battery as described in the embodiment of the second aspect.

[0020] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide further understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0022] Figure 1 It is a schematic diagram of the structure of a negative electrode sheet provided by an embodiment of the present application;

[0023] Figure 2 It is a schematic diagram of the structure of a negative electrode plate provided in another embodiment of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0025] It is understood that although the functional modules are divided in the device schematic diagram and the logical order is shown in the flow chart, in some cases, the steps shown or described may be performed in a different order than the module division in the device or the order in the flow chart. The terms "first", "second", etc. in the specification, claims or the above drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.

[0026] The embodiment of the present application provides a negative electrode plate, a battery, and an electrical device. By alternately setting a first active coating layer and a second active coating layer with different particle sizes of active material particles on the surface of the current collector along the second direction, the characteristics of the first active coating layer and the second active coating layer are different. By controlling Ds2 / Ds1≤0.5 and D502 / D501≥1.3, the particle size of the second active coating layer is relatively large, which is conducive to the storage of the electrolyte, and the ion impedance is low, which can provide an ion channel for the movement of ions, and can effectively improve the kinetic performance of the battery cell, while reducing the electrolyte transport path of the first active coating layer and improving the kinetic performance. At the same time, since the particle size of the first active coating layer is relatively small and the compaction density is large, the energy density of the battery can be improved.

[0027] Reference Figure 1 , Figure 1 It is a schematic diagram of the structure of a negative electrode plate provided in an embodiment of the present application.

[0028] It can be understood that the negative electrode sheet includes a current collector 100 and a negative electrode active material layer 200 coated on at least one surface of the current collector 100. The thickness direction of the current collector 100 is a first direction, and the negative electrode active material layer 200 includes a first active coating 210 and a second active coating 220 alternately arranged in a second direction perpendicular to the first direction. That is, the negative electrode active material layer 200 includes a plurality of first active coatings 210 and a plurality of second active coatings 220, and the plurality of first active coatings 210 and the plurality of second active coatings 220 are alternately arranged, and the thickness direction of the first active coating 210 and the thickness direction of the second active coating 220 are the same as the thickness direction of the current collector 100. By setting the direction in which the first active coating 210 and the second active coating 220 are alternately arranged perpendicular to the thickness direction of the current collector 100, the electrolyte can contact the first active coating 210 and the second active coating 220 at the same time. In addition, the active material particles of the first active coating 210 and the active material particles of the second active coating 220 satisfy that the ratio of Ds2 to Ds1 is less than or equal to 0.5, and the ratio of D502 to D501 is greater than or equal to 1.3, wherein Ds2 = D902-D102, Ds1 = D901-D101; D101 is the particle size corresponding to the cumulative particle size distribution percentage of the active material particles of the first active coating 210 reaching 10%, and D501 is the particle size corresponding to the cumulative particle size distribution percentage of the active material particles of the first active coating 210 reaching 5 D901 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating 210 reaches 90%, D102 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating 220 reaches 10%, D502 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating 220 reaches 50%, and D902 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating 220 reaches 90%.

[0029] It can be understood that by controlling the active material particles of the first active coating 210 and the active material particles of the second active coating 220 to satisfy the ratio of Ds2 to Ds1 being less than or equal to 0.5, the particle stacking of the active material particles in the first active coating 210 is denser than the particle stacking of the active material particles in the second active coating 220, so that the energy density of the first active coating 210 is greater than the energy density of the second active coating 220. Since the particle size distribution of the active material particles in the second active coating 220 is more concentrated, it is beneficial to the storage of the electrolyte and the ion transport, thereby improving the kinetic performance of the battery.

[0030] It is understandable that the smaller the particle size of the active material particles of the active coating, the greater the compaction density of the active coating, and thus the kinetic performance of the battery will decrease but the energy density will increase. The larger the particle size of the active material particles of the active coating, the smaller the compaction density of the coating, the higher the efficiency of ion passage, and thus the higher the kinetic performance of the battery. Therefore, by controlling the active material particles of the first active coating 210 and the active material particles of the second active coating 220 to satisfy the ratio of D502 to D501 greater than or equal to 1.3, the material structure can be not destroyed while ensuring the kinetic performance of the battery, and the self-discharge performance and service life of the battery will not be reduced.

[0031] Specifically, in some embodiments, the second direction can be the length direction of the current collector 100, that is, the first active coating 210 and the second active coating 220 are alternately arranged along the length direction of the current collector 100, and the total width of multiple first active coatings 210 and multiple second active coatings 220 is equal to the length of the current collector 100, and the length of the first active coating 210 and the length of the second active coating 220 are equal to the width of the current collector 100.

[0032] It should be noted that if Figure 2 As shown, Figure 2 It is a structural schematic diagram of the negative electrode plate provided by another embodiment of the present application. The second direction can also be the width direction of the current collector 100, that is, the first active coating 210 and the second active coating 220 are alternately arranged along the width direction of the current collector 100, and the total width of the multiple first active coatings 210 and the multiple second active coatings 220 is equal to the width of the current collector 100, and the length of the first active coating 210 and the length of the second active coating 220 are equal to the length of the current collector 100.

[0033] It should be noted that the particle size of the active material particles of the first active coating 210 and the particle size of the active material particles of the second active coating 220 are screened by screening equipment. If the particle size is smaller, the screening is more difficult. At the same time, if the particle size distribution of the active material particles in the active coating is more dispersed, the improvement effect of the kinetic properties of the active coating will be worse. Therefore, the value range of Ds2 should be 1.5 to 10 (including 1.5 and 10); similarly, in order to ensure the improvement effect of the kinetic properties of the negative electrode plate, the ratio range of Ds2 to Ds1 is preferably 0.1 to 0.5 (including 0.1 and 0.5).

[0034] It should be noted that the smaller the particle size of the active material particles in the active coating, the more difficult it is to screen them. At the same time, the larger the particle size of the active material particles in the active coating, the lower the energy density of the battery cell. In addition, during the rolling process, the larger the particle size of the active material particles in the active coating, the higher the risk of the active coating breaking. Therefore, the ratio range of D502 / D501 is preferably 1.3 to 2 (including 1.3 and 2).

[0035] Specifically, in some embodiments, the first active coating 210 and the second active coating 220 are controlled to satisfy any one of the conditions of 0.1≤Ds2 / Ds1≤0.5, 1.3≤D502 / D501≤2, and 1.5≤Ds2≤10.

[0036] Specifically, in some embodiments, the first active coating 210 and the second active coating 220 are controlled to satisfy any two conditions of 0.1≤Ds2 / Ds1≤0.5, 1.3≤D502 / D501≤2, and 1.5≤Ds2≤10.

[0037] Specifically, in some embodiments, the first active coating 210 and the second active coating 220 are controlled to satisfy 0.1≤Ds2 / Ds1≤0.5, 1.3≤D502 / D501≤2, and 1.5≤Ds2≤10.

[0038] It is understandable that, since the particle size of the active material of the second active coating 220 is larger than the particle size of the active material of the first active coating 210, the greater the width of the first active coating 210, the greater the energy density of the battery. However, due to the increase in the width of the first active coating 210, the width of the second active coating 220 will decrease when the length of the current collector 100 remains unchanged. The decrease in the width of the second active coating 220 will reduce the ion diffusion rate and the storage space of the electrolyte, thereby causing the battery's kinetic performance to decrease. Therefore, the ratio of W1 to W2 should be less than or equal to 5, where the width of the first active coating 210 is W1 mm ​​and the width of the second active coating 220 is W2 mm.

[0039] Specifically, in order to ensure the energy density of the battery while providing a higher ion diffusion rate and more electrolyte storage space, the width W2 of the second active coating 220 can be controlled to be in the range of 1 mm to 3 mm and / or the ratio of the width W1 of the first active coating 210 to the width W2 of the second active coating 220 can be controlled to be less than or equal to 5 but greater than or equal to 1.

[0040] It is understood that the active material of the first active coating 210 and the active material of the second active coating 220 can be at least one of artificial graphite, natural graphite, hard carbon and silicon-based materials, wherein the active material of the first active coating 210 and the active material of the second active coating 220 are the same material. The conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene; the binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose and polymethyl methacrylate. In some embodiments, the active material includes a silicon-based material, for example, a silicon-carbon material with a core-shell structure or a silicon-carbon material of porous carbon-deposited silicon.

[0041] Specifically, in some embodiments, the active material used in the active coating includes a silicon-carbon material with a core-shell structure or a silicon-carbon material with porous carbon-deposited silicon. If laser drilling is used to improve the dynamic performance of the battery, the carbon matrix around the nano-silicon and the coating layer on the surface of the composite material will be damaged during the laser drilling process, thereby directly exposing the active nano-silicon to the air and electrolyte environment, reducing the service life of the battery. However, the technical solution of alternately setting multiple first active coatings 210 and multiple second active coatings 220 of the present application and controlling the ratio of Ds2 to Ds1 to be less than or equal to 0.5 and the ratio of D502 to D501 to be greater than or equal to 1.3 will not damage the carbon matrix around the nano-silicon and the coating layer on the surface of the composite material.

[0042] In order to further explain the present application in detail, the present application will be further explained in conjunction with specific examples. The experimental methods used in the examples of the present application are all conventional methods unless otherwise specified; other materials, reagents, etc. used in the examples of the present application are all purchased from the market unless otherwise specified.

[0043] Example 1

[0044] This embodiment provides a battery, which includes an electrode assembly formed by winding a positive electrode sheet and a negative electrode sheet, a separator is provided between the positive electrode sheet and the negative electrode sheet, and the battery is filled with an electrolyte.

[0045] The preparation method is as follows:

[0046] (1) Preparation of positive electrode sheet: The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride are mixed in an N-methylpyrrolidone solvent system at a mass ratio of 95:3:2, and then coated on a positive electrode current collector. The material of the positive electrode current collector is aluminum foil. After drying, cold pressing, and slitting, a positive electrode sheet is obtained.

[0047] (2) Preparation of negative electrode sheet: artificial graphite and porous carbon deposited silicon carbon material were mixed in a mass ratio of 9:1 and sieved through a sieving device to obtain a first negative electrode active material with D101 of 5.5 μm, D501 of 13.5 μm and D901 of 28.5 μm. Artificial graphite and porous carbon deposited silicon carbon material were mixed in a mass ratio of 9:1 and sieved through a sieving device to obtain a second negative electrode active material with D102 of 18.5 μm, D502 of 21.6 μm and D902 of 24.7 μm.

[0048] The first negative electrode active material, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5 to obtain a first active coating slurry. The second negative electrode active material, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5 to obtain a second active coating slurry. The first active coating slurry and the second active coating slurry are alternately coated on the surface of the negative electrode collector along the length direction of the electrode sheet by electrostatic spraying, dried, cold pressed, and stripped to obtain a negative electrode sheet having a first active coating and a second active coating alternately arranged along the length direction of the electrode sheet. In this embodiment, the negative electrode collector is a copper foil with a thickness of 6μm, and both surfaces of the collector are coated with a first active coating and a second active coating alternately arranged along the length direction of the electrode sheet. In this embodiment, the first active coating formed by the first active coating slurry has a width W1 of 1 mm in the length direction of the pole piece, and the second active coating formed by the second active coating slurry has a width W2 of 1 mm in the length direction of the pole piece. The first active coating slurry and the second active coating slurry can also be alternately coated on the surface of the negative electrode current collector along the length direction of the pole piece by 3D printing or extrusion die.

[0049] (3) Selection of isolation membrane

[0050] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0051] (4) Preparation of electrolyte

[0052] Add lithium salt LiPF6 to a non-aqueous organic solvent (ethylene carbonate (EC): fluoroethylene carbonate (FEC): diethyl carbonate (DEC): propylene carbonate (PC): dimethyl carbonate (DMC) = 1:1:1:1:1, weight ratio), the concentration of LiPF6 is 1 mol / L, and mix well.

[0053] (5) Preparation of lithium-ion secondary batteries

[0054] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging shell, the electrolyte is injected and packaged to obtain a lithium-ion secondary battery.

[0055] Example 2

[0056] The difference between Example 1 and Example 2 is that the width W1 of the first active coating formed by the first active coating slurry in Example 2 in the length direction of the pole piece is 3 mm, and the width W2 of the second active coating formed by the second active coating slurry in the length direction of the pole piece is 3 mm. The rest is the same as Example 1 and will not be repeated.

[0057] Example 3

[0058] The difference between Example 1 and Example 3 is that the width W1 of the first active coating formed by the first active coating slurry in Example 3 in the length direction of the pole piece is 5 mm, and the width W2 of the second active coating formed by the second active coating slurry in the length direction of the pole piece is 1 mm. The rest is the same as Example 1 and will not be repeated.

[0059] Example 4

[0060] The only difference between Example 1 and Example 4 is that the second active material in the negative electrode sheet of Example 4 has a D102 of 14.8 μm, a D502 of 18 μm and a D902 of 21.2 μm, and the active materials with the above particle sizes are obtained by sieving through a sieving device. The rest is the same as Example 1 and will not be described again.

[0061] Example 5

[0062] The only difference between Example 1 and Example 5 is that the second active material in the negative electrode sheet of Example 5 has a D102 of 18.5 μm, a D502 of 19.85 μm and a D902 of 21.2 μm, and the active materials with the above particle sizes are obtained by sieving through a sieving device. The rest is the same as Example 1 and will not be described again.

[0063] Example 6

[0064] The only difference between Example 1 and Example 6 is that the second active material in the negative electrode sheet of Example 6 has a D102 of 14.8 μm, a D502 of 19.78 μm and a D902 of 24.7 μm, and the active materials with the above particle sizes are obtained by sieving through a sieving device. The rest is the same as Example 1 and will not be described again.

[0065] Example 7

[0066] The only difference between Example 1 and Example 7 is that the width W1 of the first active coating formed by the first active coating slurry in Example 7 in the length direction of the pole piece is 5 mm, and the width W2 of the second active coating formed by the second active coating slurry in the length direction of the pole piece is 5 mm. The rest is the same as Example 1 and will not be repeated.

[0067] Example 8

[0068] The only difference between Example 1 and Example 8 is that the width W1 of the first active coating formed by the first active coating slurry in Example 8 in the length direction of the pole piece is 7 mm, and the width W2 of the second active coating formed by the second active coating slurry in the length direction of the pole piece is 1 mm. The rest is the same as Example 1 and will not be repeated.

[0069] Comparative Example 1

[0070] The only difference between Example 1 and Comparative Example 1 is that the D102, D502 and D902 of the second active material in the negative electrode sheet of Comparative Example 1 are 14.8 μm, 16.65 μm and 18.5 μm, and the active materials with the above particle sizes are obtained by sieving through a sieving device. The rest is the same as Example 1 and will not be repeated.

[0071] Comparative Example 2

[0072] The only difference between Example 1 and Comparative Example 2 is that the D102, D502 and D902 of the second active material in the negative electrode sheet of Comparative Example 2 are 10.6 μm, 20.15 μm and 29.7 μm, and the active materials with the above particle sizes are obtained by sieving through a sieving device. The rest is the same as Example 1 and will not be repeated.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that the active material layer of the negative electrode plate of Comparative Example 3 is formed by the first active coating slurry, and does not contain the second active coating. The rest is the same as Example 1 and will not be described again.

[0075] Comparative Example 4

[0076] The difference between Comparative Example 4 and Example 1 is that the active material layer of the negative electrode sheet of Comparative Example 4 is formed by the first active coating slurry, and does not contain the second active coating. In addition, the surface of the active material layer of Comparative Example 4 is laser-drilled, and the drilling depth is 20% of the coating thickness. The rest is the same as Example 1 and will not be repeated.

[0077] The parameters of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1.

[0078]

[0079] Table 1

[0080] The batteries provided in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to lithium deposition tests, and the lithium deposition test method was as follows:

[0081] At room temperature, perform the following steps:

[0082] 1. XC rate constant current charging to 4.5V, 4.5V constant voltage charging until the current is lower than 0.05C;

[0083] 2. Leave for 10 minutes;

[0084] 3. 0.7C constant current discharge to 3.0V;

[0085] 4. Leave for 10 minutes;

[0086] 5. Repeat steps 1 to 4 20 times;

[0087] 6. 0.5C constant current charge to 4.5V, 4.5V constant voltage charge until the current is lower than 0.05C.

[0088] Among them, X is 2.5, 3, 3.5, 4, and 4.5 respectively.

[0089] The results are shown in Table 2:

[0090]

[0091]

[0092] Table 2

[0093] Among them, slight lithium deposition means that only slight lithium deposition occurs at the head and tail of the pole piece, and no lithium deposition occurs in other places; moderate lithium deposition means that lithium deposition occurs at the head and tail of the pole piece and the pole ears, and no lithium deposition occurs on the large surface; severe lithium deposition means that lithium deposition occurs at the head and tail of the pole piece, the pole ears and the large surface.

[0094] It can be seen from Table 2 that when the first active coating and the second active coating satisfy the following conditions: Ds2 / Ds1≤0.5, D502 / D501≥1.3, the lithium plating improvement effect of laser drilling can be achieved.

[0095] The batteries provided in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to self-discharge tests, and the self-discharge test method is as follows:

[0096] At room temperature, charge at a constant current of 0.5C until the voltage reaches 4.0V, and then charge at a constant voltage of 4.0V until the current is lower than 0.05C, and then place in a 45℃ environment for 24h, and then transfer to 25℃ for 24h, record the voltage after the shelf as OCV1, and finally place the battery cell in 25℃ for 48h, record the voltage after the shelf as OCV2, and calculate the K value. Among them, K value = (OCV2-OCV1) / 48h, in mV / h.

[0097] The results are shown in Table 3:

[0098] K Value K value change percentage Example 1 0.0229 -5.80% Example 2 0.0233 -4.10% Example 3 0.0239 -1.60% Example 4 0.0238 -2.10% Example 5 0.0231 -4.90% Example 6 0.0233 -4.10% Example 7 0.0235 -3.30% Example 8 0.0242 -0.40% Comparative Example 1 0.0241 -0.80% Comparative Example 2 0.0239 -1.60% Comparative Example 3 0.0243 0.00% Comparative Example 4 0.0311 28%

[0099] Among them, the larger the K value, the higher the self-discharge rate, the percentage change of K value = (k value of each group of embodiments or comparative examples - k value of comparative example 3) / K value of comparative example 3 * 100%, the smaller the percentage change of K value, the smaller the K value, and the smaller the K value, the better the self-discharge performance.

[0100] As can be seen from Table 2, both the present application and laser drilling can improve the dynamic performance of the battery cell and reduce the risk of lithium plating. However, from Table 3, while laser drilling improves the dynamic performance of the battery cell, it will have a greater impact on the self-discharge, while the present application can effectively improve the self-discharge performance compared to laser drilling while improving the dynamic performance of the battery cell. Batteries with higher self-discharge rates will lose their capacity faster during storage, which will not only affect the battery's endurance, but may also cause the battery to fail to meet the expected power requirements after a long period of non-use, reducing the battery's service life.

[0101] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0102] The above is a specific description of the preferred implementation of the present application, but the present application is not limited to the above-mentioned implementation mode. Technical personnel familiar with the field can also make various equivalent deformations or substitutions without violating the spirit of the present application. These equivalent deformations or substitutions are all included in the scope defined by the claims of the present application.

Claims

1. A negative electrode plate, characterized in that: include: A current collector, wherein the thickness direction of the current collector is a first direction; A negative electrode active material layer is disposed on at least one surface of the current collector; The negative electrode active material layer includes a first active coating layer and a second active coating layer alternately arranged in a second direction perpendicular to the first direction, and the first active coating layer and the second active coating layer satisfy: Ds2 / Ds1≤0.5, D502 / D501≥1.3, wherein Ds2=D902-D102, Ds1=D901-D101; D101 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 10%, D501 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 50%, D901 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the first active coating reaches 90%, D102 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 10%, D502 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 50%, and D902 is the particle size corresponding to when the cumulative particle size distribution percentage of the active material particles of the second active coating reaches 90%.

2. The negative electrode sheet according to claim 1, characterized in that: In the alternating arrangement direction of the first active coating layer and the second active coating layer, the width of the first active coating layer is W1 mm, the width of the second active coating layer is W2 mm, and W1 / W2≤5.

3. The negative electrode sheet according to claim 1, characterized in that: 0.1≤Ds2 / Ds1≤0.5; and / or, 1.3≤D502 / D501≤2; And / or, 1.5≤Ds2≤10.

4. The negative electrode sheet according to claim 1, characterized in that: In the alternating arrangement direction of the first active coating layer and the second active coating layer, the width of the first active coating layer is W1 mm, the width of the second active coating layer is W2 mm, and 1≤W1 / W2≤5; And / or, the width W2 mm of the second active coating is 1-3 mm.

5. The negative electrode sheet according to claim 1, characterized in that: The active material of the first active coating layer and the active material of the second active coating layer are independently selected from at least one of artificial graphite, natural graphite, hard carbon and silicon-based materials.

6. The negative electrode sheet according to claim 5, characterized in that: The active material of the first active coating layer and the active material of the second active coating layer are the same material; and / or, the active material of the first active coating layer and the active material of the second active coating layer include silicon-based materials.

7. The negative electrode sheet according to claim 6, characterized in that: The silicon-based material includes a silicon-carbon material.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The first active coating and the second active coating further include a conductive agent and a binder; the conductive agent includes at least one of conductive carbon black, carbon nanotubes, and graphene, and the binder includes at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, and polymethyl methacrylate.

9. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as described in any one of claims 1 to 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Negative plate, preparation method thereof and lithium ion battery comprising negative plate

    CN111916668A

  • Negative plate and lithium ion battery containing the same

    CN112310343A

  • Stripe pole piece, rolling process thereof and multi-tab pole piece

    CN113707839A

  • Quick-charge type negative pole piece, battery cell containing pole piece and battery

    CN115911270A

  • Negative pole piece, secondary battery and electric device

    CN115986053A

Cited By

  • Negative plate and lithium ion battery

    CN121483980A